Methods of Glycemic Control and Neonatal Outcomes after Antenatal Corticosteroid Administration among Women with Pregestational Diabetes - Battarbee, Ashley N.; Anderson, Sarah B.; Tita, Alan T.N.; Harper, Lorie M. (American Journal of Perinatology, 2019)
Objective The objective of this study was to evaluate the association between the method of maternal glycemic control after antenatal corticosteroid, administration and maternal hyperglycemia and neonatal morbidity among women with diabetes.Study Design This was a retrospective cohort study of women with pregestational diabetes who received antenatal corticosteroids and delivered in <34 weeks. The primary maternal outcome was adequate glycemic control, defined as <50% of glucose values above goal (fasting <100 mg/dL, 2-hour postprandial <120 mg/dL, or <115 mg/dL on insulin infusion). The primary neonatal outcome was composite morbidity (continuous positive airway pressure, mechanical ventilation, intraventricular hemorrhage, or death). Demographic characteristics and outcomes were compared by the method of glycemic control and neonatal morbidity using chi-square test, Fisher's exact test, Mann–Whitney U-test, and Student's t-test, as appropriate.Results Of 52 eligible women, only 1 (1.9%) had adequate maternal glycemic control. There was no significant association between the method of glycemic control and maternal hyperglycemia or neonatal morbidity. There was no association between maternal glucose and neonatal morbidity; however, neonates with composite morbidity were more likely to be born to women who received less insulin.Conclusion Maternal glycemic control among women with diabetes was poor after the antenatal corticosteroid administration, regardless of glycemic control method. Neither the method of maternal glycemic control nor the degree of control was associated with neonatal morbidity.
Keywords: antenatal corticosteroids; diabetes; glycemic control; insulin; preterm birth